RADAR-BASED RAINFALL ESTIMATION IN BOYONG RIVER (BO-D5) - Henggar Risa Destania; Achmad Syarifudin (Asosiasi Peneliti Sriwijaya, 2022)
Sediment-related disasters are terrible disasters that can catastrophically impact facilities. People must keep in mind to make sediment-related disaster information that can be predicted from rainfall and response of drainage area by using snakelike. This research produces important indices on precipitation related to debris. It shows the current status of the stage of the response of drainage area against rainfall by using a couple of short- and long-term indices. It shows the water storage volume in the soil layer with the calculation of soil water index (SWI) by using X-band MP (Multi-Parameter) rainfall radar data that has been installed at the top of Merapi Mountain (Merapi Museum). It was confirmed that from June 2018 – June 2019, with 80.28 mm SWI, maximum values do not exceed the standard reference value of SWI (120 – 160 mm) set from JMA. It means that 80.28 mm of SWI value has not yet become the maximum limit of SWI value for lahar occurrence in the Boyong drainage area (BO-D5). The maximum limit of SWI value can be generated if sediment disaster occurrences are available.